Expedition Arctic Ocean 2016 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during August to September 2016 - Gårdfeldt, Katarina; Dickson, Mary-Lynn (Swedish Polar Research Secretariat, 2018)
Arctic Ocean 2016 is a polar research expedition in collaboration with Canada with the two icebreakers Oden and Louis S. St-Laurent.

The icebreaker Oden will depart from Longyearbyen, Svalbard, 8 August to meet up with the Canadian icebreaker Louis S. St-Laurent and launch the expedition. For six weeks, the vessels will operate in the Arctic Ocean, mainly in the Amundsen Basin and in areas around the underwater mountain ranges Lomonosov Ridge and Alpha Ridge.

The aim of the Canadian research programme is to collect data in support of Canada’s extended continental shelf submission to the Commission on the Limits of the Continental Shelf, prepared in accordance with the United Nations Convention on the Law of the Sea (UNCLOS). The Swedish research is focused on environmental chemistry, marine geology and atmospheric research. On board Oden there will also be Danish and Norwegian researchers working with marine geology and ice management.

This dataset contains meteorological, oceanographic and ship data collected during the Canadian-Swedish expedition Arctic Ocean 2016, which was an international research cruise using the icebreaker Oden.

Data include:

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on the instrumentation and the individual variables can be found in the info file. Graphics and files describing the route can found in the package.

Arctic Ocean 2016 var en forskningsexpedition som, i samarbete med Kanada, avgick sommaren 2016 med de båda isbrytarna Oden och Louis S. St-Laurent.

Isbrytaren Oden avreser från Longyearbyen på Svalbard 8 augusti för att möta upp den kanadensiska isbrytaren Louis S. St-Laurent och inleda expeditionen. Fartygen kommer att arbeta i Arktiska oceanen, främst i Amundsenbassängen och områdena kring undervattensbergskedjorna Lomonosovryggen och Alfaryggen. Expeditionen pågår i sex veckor.

Syftet med det kanadensiska forskningsprogrammet var att samla in data om den kanadensiska kontinentalsockelns utsträckning. Insamlad data kommer att ligga till grund för Kanadas anspråk på områden som är en förlängning av landets kontinentalsockel enligt FN:s havsrättskonvention. De svenska forskningsprojekten hade inriktning på miljökemi, maringeologi och atmosfärforskning. Ombord fanns även danska och norska forskningsprojekt inom maringeologi respektive isteknik.

This dataset contains meteorological, oceanographic and ship data collected during the Canadian-Swedish expedition Arctic Ocean 2016, which was an international research cruise using the icebreaker Oden.

Data include:

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on the instrumentation and the individual variables can be found in the info file. Graphics and files describing the route can found in the package.
Arctic Ocean 2016 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden - Expedition Arctic Ocean 2016 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during August to September 2016
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; CLOUDS; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; DENSITY; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö